Development of a process to obtain biogas by reusing textile fiber waste (Nexo Revista Científica, 2023)
A sustainable process was designed and developed for the generation of renewable energy through residual natural fiber from the spinning process. Currently, companies in the textile sector in Arequipa do not responsibly manage the solid waste generated in the spinning process for the manufacture of garments; these companies do not have adequate disposal procedures, so most of this waste ends up in municipal landfills, generating logistical costs for proper disposal or simply being burned in the open air, generating pollutants such as carbon dioxide and methane, which have a negative impact on the environment. After carrying out a situational diagnosis and analyzing several success cases collected on the use of textile fiber and its effect on obtaining renewable energies, a process divided into two units was designed: the first pre-treatment unit covers from the preparation of the culture medium to the collection of residual textile fiber from alpaca and sheep wool; and the second treatment unit, which covers from the inoculation of the digester to obtaining biogas/biol. Finally, this process was validated by means of a modeling in the Visio Process Simulator engineering software, considering different variability scenarios. Preliminary results show that the proposal is viable both technically and economically because the textile fiber has a great energy potential with which biogas can be obtained through an eco-friendly process using biodigesters through anaerobic digestion.